Exogenous application of abscisic acid to root systems of grapevines with or without salinity influences water relations and ion allocation. (24th January 2017) - Degaris, K. A.; Walker, R.R.; Loveys, B.R.; Tyerman, S.D.
Abstract : Abstract: Background and Aims: Exposure to salinity or water deficit is known to increase the concentration of abscisic acid (ABA) within grapevines. Elevated plant ABA has alone been shown to reduce the flux of chloride from roots to shoots. The aim was to evaluate the effect of exogenously applied ABA to grapevine root systems, with or without saline irrigation water, on water relations and ion allocation. Methods and Results: Vitis vinifera (Shiraz, clone EVOVS12) vines on own roots were treated with a control of nutrient solution only, and with other treatments, also in nutrient solution, consisting of 75 mmol/L chloride (Cl − ) salts [cations: 45 mmol/L sodium (Na + ), 7.5 mmol/L calcium (Ca ++ ), 7.5 mmol/L magnesium (Mg ++ )], 50 and 100 μmol/L ABA, and 75 mmol/L Cl − salts plus 50 and 100 μmol/L ABA, all applied by watering to roots of potted vines in a glasshouse. Treatments were applied for 14 days before the plants were destructively harvested for ion analysis. All applied treatments reduced stomatal conductance, assimilation and transpiration, but ABA plus Cl − salts did not result in further reduction compared with that of ABA alone. Abscisic acid, only in the presence of salt, reduced Cl − concentration in all vine structures except the roots, while the concentration of Na +, K + and Ca ++ was less affected. This reduction could not be accounted for by reduced transpiration. Conclusion: In the presence of excess Cl − salts, ABA applied exogenously to Shiraz roots reduced Cl − transport to the shoot. Significance of Study: This provides some insight into the ability of deficit irrigation techniques to modify water relations and ion concentration.